Desempeño financiero de la empresa camaronera San Alfonso post covid-19: liquidez, endeudamiento y rentabilidad. - Tacuri Pazmiño, Camila Abigail; Ochoa Fernandez, Nayeli Elizabeth (Machala : Universidad Técnica de Machala, 2023)
In Ecuador, shrimp farming has gained significant importance over time as it contributes significantly to the country's economy and GDP. For this reason, it is essential for companies engaged in this activity to efficiently manage their costs and expenses. They should conduct timely and appropriate financial analysis to evaluate their financial performance and determine business growth in this competitive market. Based on the information previously presented, the purpose of this thesis is to analyze the financial performance of the shrimp farming company San Alfonso S.A. in the province of El Oro during the periods of 2020 and 2021. This analysis will be conducted by applying Financial Ratios to their financial information to assess their liquidity, profitability, and post-pandemic indebtedness, with the aim of identifying how these factors influenced the company's growth. The methodology employed, in line with the established variables, utilizes a quantitative approach that allows the researcher to carry out an evaluation, comprehension, and statistical examination of the company's financial information. The explanatory method aims to explain the causes of the problem or various consequences related to it, including the interpretation of the challenges faced during the COVID-19 pandemic. Following the analysis of the financial performance and in accordance with the results obtained, it was determined that the company faces a fund shortage due to insufficient income to cover its financial expenses. Consequently, the existing liquidity only covers short-term debts. Regarding profitability, there has been an improvement, but it still remains a disadvantage in terms of generating profits with fewer assets. Additionally, the company's level of indebtedness is very high due to the need to increase production.
En el Ecuador la actividad camaronera ha tomado una gran importancia con el pasar del tiempo puesto que es un aporte relevante en la economía del país y el PIB, por esta razón es necesario que las empresas que se dedican a esta actividad se encarguen de manejar de manera eficiente y eficaz su costos y gastos, de modo que realicen un análisis financiero adecuado y oportuno para evaluar el desempeño financiero y así puedan determinar el crecimiento empresarial en este mercado rival existente. A raíz de la información previamente expuesta, el propósito del trabajo de titulación consiste en analizar el desempeño financiero de la empresa camaronera San Alfonso S.A. de la provincia de El Oro en los periodos 2020 y 2021 mediante la aplicación de Ratios Financieros en su información financiera para conocer su liquidez, rentabilidad y endeudamiento post pandemia, con el fin de identificar como estos factores influyeron en el crecimiento de la entidad. La metodología empleada en concordancia a las variables establecidas, se aplica un enfoque cuantitativo que permite llevar a cabo al investigador un procedimiento de evaluación, compresión y examen estadístico de la información financiera de la empresa. El método explicativo donde se tiene como objetivo la explicación de las causas del problema o consecuencias varias que se relacionan a la misma, es decir la interpretación de los problemas que se vivió en el caso de la pandemia COVID-19. Tras el análisis del desempeño financiero y acorde a los resultados obtenidos se determinó que la empresa presenta una escasez de fondos creada por la insuficiencia de ingresos para cubrir sus gastos financieros, por lo cual la liquidez existente abarca las deudas en un plazo corto, en cuestión de rentabilidad ha existido una mejora pero aun así sigue siendo una desventaja en capacidad a la elevación de los beneficios con menos activos, y el endeudamiento de la empresa manifiesta un nivel muy alto en función a la necesidad por aumentar la producción.
Keywords: LIQUIDEZ; RENTABILIDAD; ENDEUDAMIENTO; PANDEMIA